Organizational Behavior in Administrative Services (Study of Services For Driving License (SIM) at Sukabumi City Police) - Neni Rosmiati (Universitas Syiah Kuala, 2023)
In Organizational behavior is a function of the interaction between individuals and their environment. The purpose of this research is to find out how organizational behavior is in the Services for Making Driving Permits (SIM) at Sukabumi Porles. The administrative service for making driving licenses is carried out with the intent and purpose of achieving administrative order, to obtain accurate SIM making data as a basis for making decisions, the result of registration of the people of Sukabumi City is the issuance of proof of a valid driving license and valid personal identity is the basis to take care of the interests of making a SIM for the Sukabumi City Community concerned. The research method used is descriptive method with a qualitative data analysis approach. From the discussion it can be concluded that organizational behavior at the Sukabumi City Police Office, especially the SIM manufacturing office.still needs to be improved in order to create an orderly administration service effectively and efficiently.